2002
DOI: 10.1385/ir:26:1-3:153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Function of Transmembrane Protein Tyrosine Phosphatase CD148 in Lymphocyte Biology

Abstract: The transmembrane protein tyrosine phosphatase CD148 is expressed on numerous cell types, including most cells of the hematopoietic lineage. CD148 has been shown to regulate density-dependent inhibition of cell growth as well as cellular differentiation in nonhematopoietic cells and has been shown to regulate signal transduction processes in several nonlymphoid hematopoietic cell types. Analysis of CD148 expression on lymphoid cells has demonstrated that CD148 is expressed at low levels on T cells and that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As a consequence, disruption of the expression of this molecule induces a spurious stimulation of T-lymphocytes that induce lymphadenopathy, splenomegaly, elevated levels of plasma IgGs, severe myocarditis, and pancreatitis (74). Other negative T-cell surface molecules include CD95, CD148, killer cell inhibitory receptors, PD1, and B-and T-lymphocyte attenuator (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, disruption of the expression of this molecule induces a spurious stimulation of T-lymphocytes that induce lymphadenopathy, splenomegaly, elevated levels of plasma IgGs, severe myocarditis, and pancreatitis (74). Other negative T-cell surface molecules include CD95, CD148, killer cell inhibitory receptors, PD1, and B-and T-lymphocyte attenuator (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that CTLA-4/CD152, PD1, and B-and T-lymphocyte attenuator contribute to the down-modulation of TCR signals by recruiting phosphatases such as SHP-2 and/or PP2A (74,75). CD148, a phosphatase itself, also binds to the intracellular signaling protein syntenin (78). We are currently performing both proteomic and two-hybrid experiments to identifying the proteins involved in the CD147 route.…”
Section: Discussionmentioning
confidence: 99%
“…A focus on possible phosphorylation sites in the N-terminal has resulted in the discovery of a number of interactions and layers of regulation. Phosphorylation at tyrosine sites was shown to prevent interaction with receptor type protein tyrosine phosphates (rPTPnu) CD148 [28], and recent work pointed to an interesting interaction with ubiquitin (Ub), regulated by the N-terminal [29]. …”
Section: Mda-9/syntenin: Background On a Diverse Scaffolding Proteinmentioning
confidence: 99%
“…Direct evidence that the NTD and CTD regulate interactions between the PDZ domains of syntenin and target proteins is scarce but has been suggested by several studies. For example, tyrosine phosphorylation of the NTD has been reported to prevent the interaction of syntenin with the receptortype protein tyrosine phosphatase (rPTP) CD148, indicating that post-translational modifications of the NTD affect the interactions between the PDZ tandem and its targets (Harrod and Justement, 2002). Whether NTD phosphorylation affects the structure of the PDZ-domain tandem or oligomerization of syntenin, and thereby rPTP interactions, remains uncertain.…”
Section: A Role For the N-and C-terminal Domains Of Syntenin?mentioning
confidence: 99%